Evaluation of the work process of primary health care teams in prenatal care (Revista Contexto & Saúde, 2025)
The objective was to identify the factors associated with prenatal care based on the work process of primary health care teams in Brazil. This is a cross-sectional study with secondary data from 38,865 teams interviewed who took part in the external evaluation of the third cycle of the National Program for Improving Primary Care Access and Quality (PMAQ-AB, acronym in Portuguese) in 2017. The dependent variable was prenatal care, and the independent variables were grouped into hierarchical levels. Multiple logistic regression analysis was conducted, and the variables were classified into management and care. The care factors associated with consultation included continuing education, safety in providing care, and enough professionals. An institutionalized communication flow with the specialist team is absent in the managerial dimension. The lack of defined flows for delivery/maternity and the absence of a central regulation system for referrals, among others, contributed to the pregnant woman not having a consultation. The analysis provides input for improving work processes in prenatal care and strengthening the integration of the care network.
Keywords: Primary Health Care; Prenatal care; Health assessment